PEMBERDAYAAN IBU HAMIL MELALUI PEMANFAATAN PANGAN LOKAL SAGU MOCHI ROSELLA (GUCHIRO) SEBAGAI UPAYA PENCEGAHAN ANEMIA - Findy Hindratni (PITIMAS: Journal of Community Engagement in Health, 2026)
Anemia during pregnancy is a fundamental public health issue due to its high risk to maternal and fetal safety. Interventions using Iron-Folic Acid tablets are often hindered by low compliance caused by side effects. This community engagement program aimed to improve the knowledge and practical skills of pregnant women and health cadres in utilizing local food resources from Riau—specifically the combination of sago and roselle calyx, which are rich in iron and vitamin C—into a healthy food product called "Guchiro" (Sago Roselle Mochi) as an alternative non-pharmacological anemia prevention strategy. The activities were carried out through interactive education, product-making demonstrations, hands-on workshops, and group mentoring. The evaluation results showed an increase in partners' understanding of local food-based nutritional interventions and the acquisition of practical skills among cadres to produce hygienic, highly nutritious supplementary food. This program is recommended for continuous implementation through integration with local health posts and community-based enterprises.